إعادة التأهيل حمام الشفاء بالأغواط - بوشارب, وفاء; Belhadj, Belkacem, Directeur de thèse. (My University, 2019)
Hammams also called Moorish or Turkish baths, play an important role in the Islamic city because of its architectural, historical and social values, inherited from generation to generation. The traditional baths that we enter today are not a specialty of our time but rather an extension that goes back to a distant past. They are not limited to a specific region or people. These buildings are characterized by an ancestral architectural tradition in terms of architectural and construction systems. One of the oldest baths of LAGHOUAT, a city of Muslim tradition that has a Turkish baths like Hammam el CHIFAA, Built in 1820 by the Ottomans, it is in the center of the city and still plays its role. It is a traditional Ottoman style Hammam whose traditional architecture is very old. In order to preserve the building and preserve its heritage values, whose bathroom water is, considered the soul of his body? We will shed light on this cultural heritage and revive it through the rehabilitation and maintenance of its work and provide all the means to ensure thermal comfort and because the process of architectural rehabilitation links the preservation of value archaeological building and its use to meet the needs of modern times. The rehabilitation of the bathroom is functional and technical, by a new methodology (RehabiMed) to rehabilitate the traditional architecture in the Mediterranean countries and we have allocated a portion of the bathroom space in the hall. Treatment room, rehabilitation room, massages room and waiting room to preserve its functional value, in keeping with its history to preserve it, because this bathroom contains a treasure, old. Key words: Traditional bath, Islamic City, word3, Rehabilitation, Comfort, Thermal, Methodology RehabiMed, city of LAGHOUAT.
Laghouat : Université Amar Telidji - Département d'architecture Option : Architecture et patrimoine .